Minimizing Foreign Exchange Losses. - Furlong, William L. (The Accounting Review, 1966)
Abstract The above measures for minimizing exchange exposure do not comprise an all- inclusive list, but they do serve to illustrate possible components of a coordinated program of risk minimization. There are a number of inherent risks in doing business abroad-expropriation, price controls, governmental discrimination, inconvertibility of the currency, and gains and losses from exchange rate fluctuations. Management's greatest opportunity to minimize exchange losses is in the area of exchange exposure. The goal of management is the ideal exchange position in which no gains or losses due to exchange rate fluctuations can occur (net local currency assets less local currency fixed assets equals zero). There are some very definite measures which management can employ to minimize exchange exposure risk. Some of these measures are financial in character, such as local currency borrowing, purchases and sales of exchange forward or "swaps" contracts, cash management policies, and the use of local share ownership. Others are non-financial in character, such as the carrying of excess inventory which can be sold at increased prices if exchange rates decline or the investment of excess local currency cash in plant assets which will not depreciate in equivalent dollar value. Although these activities are classified as non-financial, the importance of the accounting system producing information on the need for and effectiveness of these measures must not be overlooked. If sound accounting information is provided to alert and capable management, there is much that can be done to realize normal profits on investment in foreign subsidiaries and minimize the effect of exchange rate fluctuations.